2017
DOI: 10.1021/acs.iecr.7b00778
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CO2 Regeneration in Single and Blended Amine Solvents with and without Catalyst

Abstract: Various single and blended amines (namely, MEA­(monoethanolamine), MEA-DEEA (2-diethylamino ethanol), MEA-MDEA (methyldiethanolamine), MEA-1DMA2P (1-dimethylamino-2-propanol)) with three types of catalysts (H-ZSM-5, MCM-41 and SO4 2–/ZrO2) were studied to determine the respective roles of catalyst and solvent in heat duty and CO2 desorption rate with an initial CO2 loading of 0.5 mol CO2/mol amine at 371 K. The results show that performance of the three catalysts in all the four investigated aqueous solution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 23 publications
2
113
1
Order By: Relevance
“…Others tried MEA + AMP solutions and it also reduced heat duty . Recently, some researchers developed CO 2 desorption analyses for MEA blended with other R 3 N, such as MEA‐DEEA and MEA‐1DMA2P with and without solid catalysts . The CO 2 desorption performance of the noncatalytic heating process indicated that the order of blended amines is 5 mol/L MEA + 1 mol/L MDEA >5 mol/L MEA + 1 mol/L 1DMA2P > 5 mol/L MEA + 1 mol/L DEEA >5 mol/L MEA .…”
Section: Introductionmentioning
confidence: 99%
“…Others tried MEA + AMP solutions and it also reduced heat duty . Recently, some researchers developed CO 2 desorption analyses for MEA blended with other R 3 N, such as MEA‐DEEA and MEA‐1DMA2P with and without solid catalysts . The CO 2 desorption performance of the noncatalytic heating process indicated that the order of blended amines is 5 mol/L MEA + 1 mol/L MDEA >5 mol/L MEA + 1 mol/L 1DMA2P > 5 mol/L MEA + 1 mol/L DEEA >5 mol/L MEA .…”
Section: Introductionmentioning
confidence: 99%
“…The results for sensible heat, heat of evaporation, and heat of reaction are listed in Table . The heat duty and average desorption rate were also compared with previous reported results by Liu, and Srisang, where solid acid catalysts were added to reduce the energy consumption of the MEA regeneration process. The results showed that the addition of 5 g HZSM‐5 in the solution could save 30.2% of sensible heat, reduce vapor consumption by 18.7%, and total energy consumption by 23.3%.…”
Section: Resultsmentioning
confidence: 98%
“…Liu et al . compared the desorption performance of MEA rich solution at 98°C using the HZSM‐5 catalyst; the results show that the CO 2 desorption rate increased 29.4% and the heat duty reduced 24.8% . Srisang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the solid acids, such as HZSM‐5, γ ‐Al 2 O 3 , and H‐Y were added to a CO 2 ‐loaded MEA absorbent to increase the regeneration rate at 95°C, with a CO 2 desorption rate improvement of 18.2% with HZSM‐5 and 24.0% with γ ‐Al 2 O 3 . Zhang et al . reported that the regeneration performance of the CO 2 ‐loaded MEA solvent was enhanced by adding solid acid catalysts, such as MCM‐41, SO 4 2− /ZrO 2 , and SAPO‐34.…”
Section: Introductionmentioning
confidence: 99%